Performance of ortet clones of Hevea brasiliensis in Dakshina Kannada - Gireesh T; Chandrasekhar T R; Manju M J; Mydin K K; Nazeer M A (PLACROSYM XXII. 22nd Biennial Symposium on Plantation Crops: Leveraging Innovation System in Plantation Sector Through Value Addition, 15-17 December 2016, Indian Council of Agricultural Research-Central Plantation Crops Research Institute, Kasaragod, India. Abstracts. p.58.)
Unique tropical climatic pattern prevailing in Dakshina Kannada (D.K) District of Karnataka State, characterised with heavy rainfall and prevalence of leaf diseases followed by long dry spell, is one of the limiting factors in rubber cultivation. The present study is aimed at developing suitable high yielding clones with Phytophthora tolerance. Ortets of polyclonal origin or plus tree selection method is expected to provide clones with broad genetic base and diverse from a base population. Sixteen ortet clones (Ayr 1, Arl 53, Ert 40, Ces 150, Ert 38, Arl 54, Pkm 16, Pov 1, Kan 46, Pkm 14, Edm 37, Ces 151, Mkm 23, Mkm 22, Tly 57 and Ces 9) selected from the traditional region along with three recommended clones (GT 1, RRIM 600 and RRII 105) as controls were evaluated over 25 years in a small scale trial at Nettanna, D.K. District of Karnataka State. Girth of trees at 125 cm from the bud union, yield (grams/tree/tap), tappability (;), bark thickness (mm) and incidence of abnormal leaf fall disease (ALF) were assessed from the replicated field trial. Analysis of variance estimates showed a critical difference of 14.8 and 28.3 (P<0.05) for girth and pooled mean dry rubber yield, respectively. Clones showed significant variability in growth (11.2;) and yield (28.3;). Ortet clone Ayr 1 registered significantly high girth (114 cm) and dry rubber yield (78 g/t/t)followed by GT 1 (girth 92 cm; yield 71 g/t/t), Arl 53 (girth 90 cm and yield 51 g/t/t), RRII 105 (girth 73 cm; yield 47 g/t/t) and RRIM 600 (girth 76 cm; yield 40 g/t/t). Percent Disease Intensity (PDI) upon Abnormal Leaf Fall Disease (ALF) caused by Phytophthora spp. was scored. The results illustrates that among the high yielding clones, second best ortet clone Arl 53 registered highest level of tolerance (12;) towards ALF disease, compared to other clones, followed by Ert 40 (25;) and Arl 54 (32;) that are comparatively less susceptible, while control clones GT 1, RRII 105 and RRIM 600 registered 44;, 42;and 96;disease incidence, respectively. High yielding ortet clones could be selected for further evaluation and confirmaiton in on farm trials. Selection of clones with vigorous growth, yield and ALF tolerance could maximize genetic gain and provide further impetus to breeders and growers. The present study could also identify potential parents which can be either utilized directly for cross breeding programmes to generate more productive progenies suitable for D.K region.
Keywords: Dakshina Kannada; Hevea brasiliensis; Ortet clones